THE ROLE OF TESTOSTERONE IN MYOCARDIAL VASCULARIZATION AND CORONARY VASODILATION IN MALE RABBITS DURING SEXUAL MATURATION - S. Това, B.; H. Injidi, M.; M. Alshathir , N.; S. Alsamaraic, E. (The Iraqi Journal of Veterinary Medicine, 1988)
It has been reported that coronary vasodilator reserve (CVDR) is reduced at the age of sexual maturity. In this report, we studied the influence of testosterone (T) and / or castration (C) on CVDR, capillary density (CD) and capillary - to fiber ratio (C/FR) in male rabbits during sexual maturation. Twenty four immature male rabbits of about similar age and weight were divided into four equal groups, treated as follows: 1) Intact + oil (T+0); 2) Castrated +, Oil (C+0); 3) Castrated + testosterone (C+T); and 4) Intact + testosterone (I+T). Testosterone was given daily for 2 months (25 ug/Kg body weight) dissolved in 0.1 ml corn oil (i.m.) to groups 3 and 4. Groups 1 and 2 received same volume of solvent. Control (baseline) coronary flow (CCF) and maximum coronary flow (MCF) "induced by reactive hyperemia" were measured in Langendorff perfused hearts. Histological sections were made to measure CD and C/FR. The results showed that CCF (ml/min/g) was reduced in I+T hearts. MCF of groups C+T and IT was significantly attenuated when compared with its val ms in groups I+0 and Cto. CD and (baseline) C/FR were both lowered in hearts of I+T group in comparison to their values in hearts of the other three groups. Data of this study suggest that, during maturation, testosterone could be one of the factors that reduces CVDR, CD and C/FR in male rabbits.